Acquired von Willebrand syndrome in monoclonal gammopathy – A scoping review on hemostatic management. Issue 2 (17th February 2021) - Abou‐Ismail, Mouhamed Yazan; Rodgers, George M.; Bray, Paul F.; Lim, Ming Y.
Abstract: Background: Acquired von Willebrand syndrome (AVWS) has been associated with monoclonal gammopathy of undetermined significance (MGUS), with limited data on its management. Methods: We conducted a systematic literature search in Medline (Ovid), Embase, and Scopus up to September 11, 2019, for studies reporting on the management of AVWS associated with MGUS (AVWS‐MGUS). Data on patient characteristics, laboratory parameters at presentation, and clinical and laboratory outcomes were extracted. Objectives: To describe the clinical presentation and outcomes of different therapeutic approaches. Results: Seventy‐five studies were included in the final review, for a total of 137 patients. Most patients had von Willebrand factor ristocetin cofactor activity <30 IU/dL (86.6%) and factor VIII levels <50 IU/dL (91.8%). Bleeding severity ranged from no bleeding (16.1%) to minor bleeding (46.4%) and major bleeding (37.5%). The overall clinical success rates for 1‐deamino‐8‐D‐arginine vasopressin (DDAVP), factor replacement therapy, and intravenous immunoglobulin (IVIG) were 43.8%, 33.3%, and 85.4%, respectively. The laboratory response rates for DDAVP, factor replacement therapy, and IVIG were 39.0%, 62.9%, and 88.6%, respectively. Several other treatments were also reported in small numbers, out of which myeloma‐directed therapies, plasma exchange, recombinant factor VIIa, and antifibrinolytics appeared most successful, while immunosuppressive agents were largely ineffective. Conclusion: IVIG appears to be an effective treatment for AVWS‐MGUS bleeding, conferring a high clinical success rate with measurable laboratory outcomes; albeit temporary. DDAVP and factor replacement therapy may be partially successful in controlling minor bleeds, but not major bleeds. Other less commonly used agents may be effective in certain cases, although data are limited.